Paracetamol exposure in pregnancy and early childhood and development of childhood asthma: a systematic review and meta-analysis. Issue 1 (26th November 2014) - Cheelo, M; Lodge, C J; Dharmage, S C; Simpson, J A; Matheson, M; Heinrich, J; Lowe, A J
Abstract : Background and objective: While paracetamol exposure in pregnancy and early infancy has been associated with asthma, it remains unclear whether this is confounded by respiratory tract infections, which have been suggested as an alternative explanation. We undertook a systematic review and meta-analysis of longitudinal studies that reported the association between paracetamol exposure during pregnancy or infancy and the subsequent development of childhood asthma (≥5 years). Methods: Two independent researchers searched the databases EMBASE and PUBMED on 12 August 2013 for relevant articles using predefined inclusion and exclusion criteria. Study quality was assessed and results were pooled using fixed effect models or random effect models when moderate between-study heterogeneity was observed. We explicitly assessed whether the observed associations are due to confounding by respiratory tract infections. Results: Eleven observational cohort studies met the inclusion criteria. Any paracetamol use during the first trimester was related to increased risk of childhood asthma (5 studies, pooled OR=1.39, 95% CI 1.01 to 1.91) but there was marked between-study heterogeneity (I 2 =63%) and only one of these studies adjusted for maternal respiratory tract infections. Increasing frequency of use of paracetamol during infancy was associated with increased odds of childhood asthma (3 studies, pooled OR=1.15, 95% CI 1.00 to 1.31 per doubling of days exposure), but in these same three studies adjusting for respiratory tract infections reduced this association (OR=1.06, 95% CI 0.92 to 1.22). Discussion: The association during early pregnancy exposure was highly variable between studies and exposure during infancy appears to be moderately confounded by respiratory tract infections. There is insufficient evidence to warrant changing guidelines on early life paracetamol exposure at this time.